Pre- and per-treatment 18F-FDG PET/CT parameters to predict recurrence and survival in cervical cancer. Issue 3 (September 2016) - Leseur, Julie; Roman-Jimenez, Geoffrey; Devillers, Anne; Ospina-Arango, Juan D.; Williaume, Daniele; Castelli, Joel; Terve, Pierre; Lavoue, Vincent; Garin, Etienne; Lejeune, Florence; Acosta, Oscar; De Crevoisier, Renaud
Abstract: Purpose: To describe the evolution and to assess the predictive value of metabolic parameters with different SUV threshold segmentations calculated from two 18F-FDG-PET/CT, one prior to and the other one during concomitant chemoradiation therapy (CCRT), for locally-advanced cervical cancer (LACC). Material and methods: 53 patients treated for LACC by CCRT underwent FDG-PET/CT before treatment (PET1) and another one at 40 Gy (PET2). The PET analyzed parameters were: maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG). MTVs were automatically segmented using various percentage SUVmax thresholds (30–70%) and fixed SUV thresholds (all voxels with SUV >1–20). The parameters' predictive capabilities for disease-free (DFS) and overall survival (OS) were assessed using the Harrell's C-index ( c ) and Cox regression model. Results: Depending on the SUVmax threshold, the relative decreases in MTV and TLG from PET1 to PET2 were, on average, 65% (range: 63–70%) and 85% (range: 83–86%), respectively. The strongest predictive threshold segmentations were 55% SUVmax in PET1 and 32% in PET2. Significant predictors of DFS in multivariate analysis ( c  = 0.82) were MTV1 (55% SUVmax) in PET1 and TLG2 (32% SUVmax) in PET2. MTV1 (55%) was the most significant OS predictor. Conclusions: MTV and TLG calculated with a threshold of 55% SUVmax and 32% SUVmax from pre- and per-treatment PET scans respectively, can be used to predict patient outcome after CCRT for LACC.